Antibiotics Resistance and Biofilm Formation Capacity of Staphylococcus spp. Strains Isolated from Surfaces and Medicotechnical Materials. (27th August 2020) - Socohou, Akim; Sina, Haziz; Degbey, Cyriaque; Nanoukon, Chimène; Chabi-Sika, Kamirou; Ahouandjinou, Hélène; Lehmane, Halfane; Baba-Moussa, Farid; Baba-Moussa, Lamine
Abstract : Staphylococcus spp. is most often implicated in nosocomial infections. The objective of this study is to evaluate the susceptibility to antibiotics and the biofilm formation capacity of staphylococci species isolated from surfaces and medicotechnical materials at the university hospital center of Abomey-Calavi/Sô-Ava in Benin. Samples were collected according to ISO/DIS14698-1 standard from the surfaces and medicotechnical materials by the dry swab method. The isolation of Staphylococcus strains was performed on Chapman agar, and their identification was performed using microscopic and biochemical methods. The susceptibility of Staphylococcus isolates to antibiotics was evaluated by the disc diffusion method according to EUCAST and CLSI recommendations. The biofilm formation was qualitatively assessed using microplates. Of the 128 surfaces and medicotechnical material samples analyzed, 77% were contaminated with Staphylococcus spp. Thirteen species of Staphylococcus were isolated in different proportions but the pediatric department was the most contaminated (33%) by S . aureus . Resistance to antibiotics considerably varies according to the species of Staphylococcus . However, antibiotics such as chloramphenicol and vancomycin are the most effective on S . aureus, whereas coagulase-negative staphylococci developed less resistance to gentamycin and ciprofloxacin. The biofilm test reveals that 37% of our isolated strains were biofilm formers. Although regular monitoring of hospital hygiene is crucial, the optimal use of antibiotics is a cornerstone of reducing antimicrobial resistance.